2013
DOI: 10.1080/02786826.2013.861892
|View full text |Cite
|
Sign up to set email alerts
|

Anisokinetic Shrouded Nozzle System for Constant Low-Flow Rate Aerosol Sampling from Turbulent Duct Flow

Abstract: An anisokinetic shrouded nozzle system was designed for sampling particles at a constant low flow rate from a ventilation duct to an aerodynamic particle sizer (APS). Shrouded anisokinetic nozzles are a means for sampling from a moving airstream with higher particle transmission than with unshrouded isokinetic nozzles. This shrouded nozzle sampling system was evaluated in an experimental ventilation duct system. Aspiration and transport efficiency measurements were made for five particle sizes in the range 1-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Aspiration ratio or aspiration efficiency was calculated to quantify the bias in the aerosol concentration entering the inlet of probe in shrouded air samplers. In other words, AR is defined as the ratio of aerosol concentration drawn (by suction) from the airstream in the wind tunnel into the inside of probe to the bulk aerosol concentration of the air stream (Sippola and Nazaroff 2014). Table 2 shows the performance of two (A and B) shrouded probes in combination with appropriate isokinetic air samplers at 5, 10, 15 and 20 m/s in terms of aspiration ratios.…”
Section: Aspiration Ratio (Ar)mentioning
confidence: 99%
See 1 more Smart Citation
“…Aspiration ratio or aspiration efficiency was calculated to quantify the bias in the aerosol concentration entering the inlet of probe in shrouded air samplers. In other words, AR is defined as the ratio of aerosol concentration drawn (by suction) from the airstream in the wind tunnel into the inside of probe to the bulk aerosol concentration of the air stream (Sippola and Nazaroff 2014). Table 2 shows the performance of two (A and B) shrouded probes in combination with appropriate isokinetic air samplers at 5, 10, 15 and 20 m/s in terms of aspiration ratios.…”
Section: Aspiration Ratio (Ar)mentioning
confidence: 99%
“…Ram, Cain, and Taulbee (1995) and Cain, Ram, and Woodward (1998) tested the shrouded air sampler for the high velocity airborne aerosols in the size of 0.1-15 mm in the wind tunnel and verified the fluid dynamics design by calculating the airflow and the aspiration efficiency of the shrouded probes. Later Sippola and Nazaroff (2014) changed the cylindrical shape of probe (in shrouded air samplers) to an isokinetic design. They compared this new design with a buttonhook isokinetic nozzle at a constant low flow rate (2.2-8.8 m/s) and reported that the probe with an isokinetic shrouded nozzle had higher particle transmission than the other nozzles for sampling particles in a wind tunnel.…”
Section: Introductionmentioning
confidence: 99%